Prognostic value of pretreatment neutrophil-to-lymphocyte ratio in patients with soft tissue sarcoma: A meta-analysis - Liu, Gang (Medicine (Baltimore), 2018)
BACKGROUND: The neutrophil-to-lymphocyte ratio (NLR) has been reported to possess significant prognostic value in multiple types of cancer. We conducted a meta-analysis to evaluate the prognostic value of pretreatment NLR in soft tissue sarcoma (STS). METHODS: A systematic literature search through April 2018 was conducted to identify studies evaluating the prognostic value of the pretreatment NLR in STS patients. The end points were overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and clinicopathological parameters. All statistical analyses were conducted with Stata 13.0. RESULTS: Fourteen cohorts with 2820 patients were analyzed. Elevated NLR was significantly correlated with worse OS [hazard ratio (HR): 1.59, 95% confidence interval (95% CI): 1.28–1.97, P < .001] and DFS/PFS (HR = 1.28; 95% CI = 1.12–1.47; P < .001). In addition, elevated NLR was highly correlated with age (≥ 65 years), tumor size (>5 cm), tumor depth (deep), Grade (G3), and TNM stage (III-IV). CONCLUSION: Overall, pretreatment NLR could be an adverse prognostic biomarker for STS.